2010
DOI: 10.1007/s11274-010-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tetracycline resistance genes in tetracycline-resistant Enterobacteriaceae obtained from a coliform collection

Abstract: Tetracycline resistance has been used as the key determinant to monitor resistance genes in natural environments such as rivers, lakes or seawater. The aim of this study was evaluate the frequency of tetA, tetB, tetC, tetD and tetE genes in 52 tetracycline-resistant Enterobacteriacea isolated from river water in the North East Black Sea Region of Turkey. In 52 tetracycline-resistant strains, resistance was mediated by tetA in eight (15.3%) strains, tetB in ten (19.2%) strains and both tetA and tetB in one (1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…The presence of tet(B), tet(E) and, rarely, tet(D) determinants has also been noted in TET R and OTC R isolates, whereas the tet(C) gene was not found. Similar results were reported by Börjesson et al [36], Sandalli et al [34] and Tao et al [19]. Auerbach et al [37] observed a wide variety of tetracycline resistance genes in wastewater, including tet(C) which was not identified in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of tet(B), tet(E) and, rarely, tet(D) determinants has also been noted in TET R and OTC R isolates, whereas the tet(C) gene was not found. Similar results were reported by Börjesson et al [36], Sandalli et al [34] and Tao et al [19]. Auerbach et al [37] observed a wide variety of tetracycline resistance genes in wastewater, including tet(C) which was not identified in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In untreated wastewater isolates, there was not the predominant gene in the TET R group, tet(A) was most frequently determined in the OTC R groups, whereas the predominance of tet(A) gene was noted in both bacterial groups from treated effluent. Sandalli et al [34] and Tao et al [19] have demonstrated the predominance of the tet(A) gene in Enterobacteriaceae bacteria, and Harnisz et al [14] -in bacteria of Aeromonas genus. The tet(A) gene, which encodes the removal of tetracyclines from the cell with the involvement of transport proteins, is often found on plasmids, including conjugating plasmids [35].…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline is the most frequently used antibiotic in veterinary medicine and in aquaculture worldwide (Miranda 2012). Sandalli et al (2010) reported that bacteria isolated from rivers of the Black Sea region of Turkey had tetA and tetB resistance genes among tested tet genes. DePaola & Roberts (1995) isolated and characterized tetracycline-resistant Gram-negative bacteria from catfish and reported that these isolates harbored either the tetD or tetE gene.…”
Section: T2mentioning
confidence: 99%
“…Currently, tetracycline resistance genes have been widely selected as an indicator to evaluate ARGs contamination [21][22][23] . Among the four kinds of tetracycline resistance genes (tetC, tetG, tetM, and tetO) tested in this study, tetC was detected in all sampling sites (both water and sediment) and tetG was also detected in all water samples which was consistent with previous studies [1,22,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%